“WORD OF MOUTH” IN ONLINE MARKETING COMMUNICATION TO IMPROVE SALES FOR THE HOSPITALITY BUSINESS INDUSTRY THROUGH PERSONAL ENGAGEMENT - Steven Gunawan; Agoes Tinus Lis Indrianto (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
A business is a company that conducts commercial, industrial, or professional operations. Businesses may be for-profit or non-profit organizations. Sole proprietorships, corporations, partnerships, and limited liability companies are the four forms of businesses that exist. To achieve great customer satisfaction, any of these sorts of enterprises in hospitality required two-way interactions involving the consumer and service provider. If the service provider fails to supply a service, the hospitality business's viability will suffer. Communication in hospitality could be challenging. Communication itself in hospitality could be delivered verbally or non-verbally depending on the present event. This study uses a qualitative approach using textual analysis for data collection. Furthermore, the study also involves analyzing location, observing company interviews, and documentation based on current events on management’s communications in an ongoing situation. This research aims to pinpoint the online marketing communication that is used to improve sales in the hospitality business through personal engagement.